English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2 answers

Two basic rules of logarithms

Ln(a) + Ln(b) = Ln(ab)
Ln(a) - Ln(b) = Ln(a/b)

So

Ln(x+12) - Ln(x+4) = Ln[(x+12)/(x+4)] = Ln(2)

(x+12)/(x+4) = 2

x+12 = 2x+8

x=4

2007-05-18 08:13:33 · answer #1 · answered by Astral Walker 7 · 1 0

Ln(x+12)-Ln(x+4)=Ln2
ln((x+12)/(x+4)) =ln 2
(x+12)/(x+4) = 2
x+12 = 2x+8
x = 4

2007-05-18 15:36:45 · answer #2 · answered by ironduke8159 7 · 0 0

fedest.com, questions and answers